If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
3*y+1 = (5/3)*y // - (5/3)*y
3*y-((5/3)*y)+1 = 0
3*y+(-5/3)*y+1 = 0
4/3*y+1 = 0 // - 1
4/3*y = -1 // : 4/3
y = -1/4/3
y = -3/4
y = -3/4
| (3x-1)/4=-5/11 | | 2/3(6y+9)=20 | | 4(x-1)-2(3x+5)=3x-1 | | a+2b=50 | | 5x=3/7 | | 5x^3=3x^2 | | 12+3p=2p+4 | | 2x=3y-10 | | A=5k/7y | | 12x-8=-20 | | 3x+5=9y-4+z | | a+a+7=3+a | | 3[4(3x+1)-(10x-9)]=7x+9 | | x=2y^2-4 | | (2x-3)/4=(3-2x)/6 | | 2x-(1/x)=1 | | x^2-x-x=0 | | 2X+7X-12=33 | | X^2-2x-12=-12 | | 7(t-6)+7t=7(2t+3)-10 | | -6=(y-4)/9 | | 1/2(4y+3)=1/4(y+8) | | 7y+12/t=36 | | 61=6x-11 | | 3(2x+1)+13x-12=18x-3 | | -1=x/3-7 | | 2-6x=-88 | | 16=6x+40 | | -(4y+2)-(-3y-8)=2 | | 4x+20=(x+3) | | 15d+2=9d+26 | | -7x^2-57x-8=0 |